Differences in solution dynamics between lens β-crystallin homodimers and heterodimers probed by hydrogen–deuterium exchange and deamidation - Lampi, Kirsten J.; Murray, Matthew R.; Peterson, Matthew P.; Eng, Bryce S.; Yue, Eileen; Clark, Alice R.; Barbar, Elisar; David, Larry L. (Biochimica et biophysica acta, 2016)
Lens transparency is due to the ordered arrangement of the major structural proteins, called crystallins. βB2 crystallin in the lens of the eye readily forms dimers with other β-crystallin subunits, but the resulting heterodimer structures are not known and were investigated in this study. Structures of βA3 and βB2 crystallin homodimers and the βA3/βB2 crystallin heterodimers were probed by measuring changes in solvent accessibility using hydrogen–deuterium exchange with mass spectrometry. We further mimicked deamidation in βB2 and probed the effect on the βA3/βB2 heterodimer. Results were confirmed with chemical crosslinking and NMR. Both βA3 and βB2 had significantly decreased deuterium levels in the heterodimer compared to their respective homodimers, suggesting that they had less solvent accessibility and were more compact in the heterodimer. The compact structure of βB2 was supported by the identification of chemical crosslinks between lysines in βB2 within the heterodimer that were inconsistent with βB2's extended homodimeric structure. The compact structure of βA3 was supported by an overall decrease in mobility of βA3 in the heterodimer detected by NMR. In βB2, peptides 70–84 and 121–134 were exposed in the homodimer, but buried in the heterodimer with ≥50% decreases in deuterium levels. Homologous peptides in βA3, 97–109 and 134–149, had 25–50% decreases in deuterium levels in the heterodimer. These peptides are probable sites of interaction between βB2 and βA3 and are located at the predicted interface between subunits with bent linkers. Deamidation at Q184 in βB2 at this predicted interface led to a less compact βB2 in the heterodimer. The more compact structure of the βA3/βB2 heterodimer was also more heat stable than either of the homodimers. The major structural proteins in the lens, the β-crystallins, are not static, but dynamic in solution, with differences in accessibility between the homo-and hetero-dimers. This structural flexibility, particularly of βB2, may facilitate formation of different size higher-ordered structures found in the transparent lens. Understanding complex hetero-oligomer interactions between β-crystallins in normal lens and how these interactions change during aging is fundamental to understanding the cause of cataracts. This article is part of a Special Issue entitled Crystallin Biochemistry in Health and Disease. [Display omitted] •βB2 crystallin is more compact in the βA3/βB2 heterodimer than in its homodimer.•Deamidation at Q184 in βB2 partially prevents the decreased solvent accessibility.•βA3 is also less accessible in the βA3/βB2 heterodimer than in the βA3 homodimer.•Crosslinking and NMR results confirm a more compact heterodimer.•The βA3/βB2 heterodimer is more heat stable than either homodimer.